STUDY OF TB STATUS IN INDONESIA AND ENDOPHYTIC ACTINOMYCETES AS POTENTIAL SOURCE OF NATURAL PRODUCT FOR ANTI-TUBERCULOSIS DRUG RESISTANCE - Ewaldo, Muhammad Farrel; Rukmana, Andriansjah; Nurkanto, Arif (Berita Biologi, 2024)
Tuberculosis, caused by Mycobacterium tuberculosis, is a significant contributor to global mortality, being responsible for one of the primary causes of death worldwide. The current problem is antibiotic resistance in the treatment of tuberculosis patients, which causes the decreasing effectiveness of drugs for tuberculosis therapy. Therefore, exploration for finding new drugs is still necessary. Actinomycetes represent a group of microbes known for producing bioactive compounds, particularly in the form of antibiotics. This microbe can be found associated with plants as endophytic actinomycetes may have the same or similar secondary metabolites as their host. In certain instances, metabolites generated by endophytic actinomycetes exhibit uniqueness and hold the potential to combat antibiotic-resistant pathogenic microbes effectively. This review focuses on new ideas for exploring the potential of endophytic actinomycetes from medicinal plants, especially in Indonesia, considering existing tuberculosis conditions using reviews from scientific sources such as scientific journals, case reports, official government websites, and tuberculosis drug development. This review was then compiled and created a new idea to explore endophytic actinomycetes from medicinal plants in Indonesia using validated methods and contemporary research.